Social construction of the image of the psychologist and of the patient: the role of implicit premises - Convertini, Josephine; Luciani, Margherita (Frontiers in Psychology, 2023)
Nowadays, there is a growing consideration of people's mental health through awareness programs, policies, and practices promoted by international aid agencies and non-governmental organizations. Psychologists and patients are major actors in mental health, and their images are socially co-constructed. Nevertheless, there is still a lot of confusion about who “psychologists” and “patients” are or what a psychologist does. This muddle may underline stereotypes and broadly speaking stigma related to mental health. Therefore, confronting directly the ideas of “psychologist” and “patient” could be a little step in challenging stereotypes and making order in the panorama of mental health. In our study, we focus on the implicit contextual premises that shape particular framings around which the images of the psychologist and of the patient are socially and culturally co-constructed. In order to reach this goal, we have investigated the discourses and the multiple points of view behind the social image of the psychologist and of the patient from different sources or contextual domains: psychology online forums, university websites, and an online survey. From a methodological perspective and according to the pragma-dialectical approach, we have identified all the different standpoints and arguments related to the various conceptions of the psychologist and the patient. We have made explicit the implicit premises that lay behind each argumentative inference via the Argumentum Model of Topics. Based on these analyses, we have reconstructed the distinct framings at stake in the different contextual domains. The findings show that implicit contextual premises have huge power in constructing stigmatization in the ideas that lay people have toward the image of the psychologist and of the patient. In particular, we have observed that the more the contextual domain is defined, the more institutional premises dominate over individual ones; on the contrary, in informal contextual domains, heterogenous individual premises are prominent. Our study underlines that it is only by substituting old implicit premises with new unimagined ones that we can change subjacent contextual premises at the very core of stigma and the prototypical world's images.